Gamification in Education - Christopoulos Athanasios; Mystakidis Stylianos (MDPI, 2025)
Gamification, or gameful design, refers to the strategic application of game design principles, mechanics, and elements into non-game environments. It is often facilitated using digital platforms, aiming to solve problems, increase engagement, and motivate individuals towards their goals. The technique fosters a gameful and interactive experience, enhancing perceived autonomy, competence, and relatedness among users. With roots in fields like education, business, marketing, and services, gamification is a versatile tool that serves to enrich user experience and create value in a multitude of settings. The widespread impact of gamification across various sectors has transformed traditional methods of engagement, notably in education.